The scientific controversy surrounding chloroquine and hydroxychloroquine in the treatment of Covid-19: the importance of social science studies in complex society (Simbiótica. Revista Eletrônica, 2020)
The article presents a study about the current controversy as to whether or not “Chloroquine and / or Hydroxychloroquine should be used to combat COVID-19 disease”. The theoretical framework is linked to the social studies of science, a branch of sociology that is already well consolidated internationally. The study was carried out from the speeches of researchers in the biomedical field, in an interview with journalists from four different television vehicles, during almost three months of quarantine. The method used was discourse analysis, focused on three dimensions of the controversy: scientific, political and social.Keywords: Social studies of science; controversy; chloroquine; Sociology of knowledge.